2017
DOI: 10.4236/ojn.2017.711088
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Secondary Traumatic Stress among Emergency Nurses: An Integrative Review

Abstract: Background: Emergency nurses are exposed to traumatized patients as part of their job. Secondary exposure to trauma may lead to traumatic stress similar to those experienced by the primary victim. Emergency nurses develop secondary traumatic stress symptoms more than other nurses due to nature of emergency departments. The consequences of secondary traumatic stress can be noticed at personal, interpersonal, or organizational level. Objectives: This integrative review aimed to explore the literature on the fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 33 publications
1
20
0
3
Order By: Relevance
“…Healthcare workers operating in emergency departments are at higher risk than workers from other departments of developing one or more symptoms of Vicarious Trauma or Secondary Traumatic Stress (STS) [9,10], a common occurrence during catastrophes [1]. Secondary trauma is defined as indirect exposure to trauma, through a firsthand account or narrative of a traumatic event, that may result in a set of symptoms and reactions similar to those found in people with posttraumatic stress disorder (PTSD) (e.g., re-experiencing, avoidance and hyperarousal).…”
Section: Secondary Trauma In Healthcare Workers and Emergency Workersmentioning
confidence: 99%
“…Healthcare workers operating in emergency departments are at higher risk than workers from other departments of developing one or more symptoms of Vicarious Trauma or Secondary Traumatic Stress (STS) [9,10], a common occurrence during catastrophes [1]. Secondary trauma is defined as indirect exposure to trauma, through a firsthand account or narrative of a traumatic event, that may result in a set of symptoms and reactions similar to those found in people with posttraumatic stress disorder (PTSD) (e.g., re-experiencing, avoidance and hyperarousal).…”
Section: Secondary Trauma In Healthcare Workers and Emergency Workersmentioning
confidence: 99%
“…Healthcare Workers serving in emergency departments experience a higher risk as compared to those working in other departments of developing one or more symptoms of secondary traumatic stress or vicarious trauma, a common phenomenon during such calamities (Morrison & Joy, 2016;Ornell et al, 2020;Ratrout & Hamdan-Mansour, 2017;Trzebi nski et al, 2020). Secondary trauma is the indirect exposure to trauma, through the firsthand narrative of a traumatic event, resultantly a set of reactions and symptoms like those found in the people with posttraumatic stress disorder (e.g., hyperarousal, avoidance and re-experiencing).…”
Section: Introductionmentioning
confidence: 99%
“…Factors that enhance or prevent occurrence of STS symptoms can be classified into two main clusters: personal and organizational factors (Ratrout & Hamdan-Mansour, 2017). Both types of factors have to be considered to understand the process of developing STS symptoms (Dworkin, Sorell, & Allen, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The organizational factors found to be linked to STS are trauma case load (Hensel et al, 2015), organizational support (Townsend & Campbell, 2009), clinical supervision, and relationship with colleagues (Dworkin et al, 2016). A recent systematic review of literature showed that little is known about how these factors are combined to interact or predict STS among ER nurses (Ratrout & Hamdan-Mansour, 2017) in spite of valuable theoretical models that explain development of STS. There is no agreement on factors that may predict or associate with STS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation